ETIKA BISNIS DAN KEADILAN KONSUMEN - Rodhiyah, Rodhiyah (Faculty of Social and Political Sciences Diponegoro University, 2011)
Abstract :The massive development in economic sector causes the same trend in all area of business scale; small, medium and big. In this atmosphere, all company interact with internal and external stakeholder. In order to collectively create effective communication and interaction, company and businessman need to cooperate based on moral value and ethics. This article explain that good business is not merely about how to gain excessive profit, but it also consider business ethics. The concept of 'the customer is king' also plays important role to get great revenue. This idea suggest businessman to gain, to maintain and to develop customer trust by employing morale and ethics attitude and also company' responsibility. On the other hand, government and other institutions should be steady in implementing regulation and proactive in auditing business ethics violence. Consumers also should support the implementation good business by more selective and smarter Â in dealing with unethical promotion or advertisement.Key words: Business Ethics, good businesspermalink:Â http://ejournal.undip.ac.id/index.php/forum/article/view/3160